Dental Anomalies in Permanent Teeth Associated With Nonsyndromic Cleft Lip and Palate in a Group of Colombian Children (2020)
Objectives: To assess the risk of dental anomaly presentation in permanent teeth in a group of Colombian children with nonsyndromic cleft lip and palate (NSCLP) and to determine the frequency of the anomalies according to the cleft type. Methods: An analytical matched case–control study was conducted with 210 controls and 210 patients with NSCLP. The patients were classified into 3 groups: complete right unilateral cleft lip and palate (RCLP), complete left unilateral cleft lip and palate (LCLP), and complete bilateral cleft lip and palate (BCLP). Univariate and multivariate Poisson regression models were used to analyze paired samples (Bonferroni adjustment, P =.002). Results: A high risk of finding agenesis of the maxillary lateral incisors, supernumerary teeth, microdontia of the maxillary lateral incisors, and rotation of the maxillary central incisors adjacent to the cleft (P <.0001) was observed in the patients with NSCLP. One or more dental anomalies were found in 98% of patients with BCLP, in 96% of those with LCLP, and in 87% of those with RCLP. Most of the anomalies were located on the cleft area. The incidence relative risk (IRR) of anomalies was highest in patients with BCLP (IRR: 10.5; 95% confidence interval [CI]: 6.76-16.3), followed by in those with LCLP (IRR: 8.51; 95% CI: 5.64-12.8). Conclusions: Most dental anomalies were found in the cleft area; this was expected because the cleft area was the most affected in the patients included in this study. © 2019, American Cleft Palate-Craniofacial Association.